Revealing the Overconfidence Misconception in Optics Material: Analysis of Consistency and Confidence Levels of Prospective Physics Teachers - Ramadhan Purbaya; Riskan Qadar; Zulkarnaen Zulkarnaen (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
Misconceptions in optics accompanied by high confidence levels remain a persistent concern, particularly among prospective physics teachers whose conceptual errors may be transferred to future students. This study aimed to analyze the conceptual consistency and confidence levels of Physics Education students in optics material using the Four-Tier Diagnostic Test (FTDT). A quantitative descriptive design was employed involving 37 Physics Education students from a university in East Kalimantan, selected through purposive sampling. The instrument consisted of 50 items covering five subtopics, plane mirrors, concave mirrors, convex mirrors, convex lenses, and concave lenses with a Cronbach's Alpha reliability of 0.865. Data were analyzed using descriptive statistics and Spearman correlation tests applied to 1,850 item-level responses. Results showed that 68% of responses were categorized as Consistent Scientific, 22% as Consistent Misconception, and 10% as Inconsistent, with 87% falling under High Confidence. The concave mirror subtopic recorded the highest misconception rate (35%), with the majority accompanied by high confidence. The Spearman correlation revealed a significant but weak positive relationship between conceptual consistency and confidence level (r = 0.183; p < 0.01), indicating the presence of overconfidence misconception. These findings provide empirical support that FTDT can serve as one alternative diagnostic instrument for simultaneously identifying students' conceptual consistency and confidence levels in optics material.